Comparison of three different methods for determining yeast killer toxin K1 activity and standardisation of units - Kurzweilová, H; Sigler, K (Experientia, 1995)
A new rapid assay of the yeast killer toxin K1 activity in Saccharomyces cerevisiae, the BCP (bromocresol purple) fluorescence test, was compared with two standard methods, the plating test and the well test. The BCP test is as precise as the plating test and more sensitive than the well test. Under suitable conditions, the test is universally applicable for determining the proportion of cells with a damaged plasma membrane in a population. A procedure was developed for calculating the results of all three tests in terms of a single well-defined unit (lethal or killer unit, LU).
Keywords: Saccharomyces cerevisiae; Saccharomyces cerevisiae - proteiny; Methods; metody; Killer Factors, Yeast; Saccharomyces cerevisiae Proteins; Mycotoxins; killer faktory kvasinek; mykotoxiny